A Mathematical Model of an Electoral Process and Predicting of Outcome - Emmanuel Azuaba; Abraham Augustine Ahiaba; Joseph Folake Lois; Adeyemi Sunday Olagunju; Ayodele Akanji; Emmanuel Obaro Ohwadua; Oluwatoyin Adelakun Adeyemo (Journal of Multidisciplinary Applied Natural Science, 2024)
We developed and analysed a mathematical model to study the dynamics of an electoral process and predict the outcome in Nigeria with three political parties as major actors. We model the ruling party (P1); major opposition party (P2) and minority opposition parties (P3). The model includes party campaigners of the three political parties and a class of eligible voters. The model also incorporates the Independent National Electoral Commission (INEC), electoral observers, judiciary, security personnel and thugs. The influx of voters into the system is determined by the registration rate of voter cards. The model’s interest lies in the measure of positive influence that the party campaigners who eligible voters to join their party. With this, the model mirrors election’s outcome and the movement of voters between the three groups of political parties involved. The model has proven that the pattern of election’s outcome for each political party is affected by the defection of party members and lack of policy consistency. We determine the equilibria analytically and discuss the stability of the system. Numerical simulations are graphed in combination with curve fitting to compare each party’s performances over the years. The result shows that no political party remains in power steadily from 2007 to 2019. Thus, the prediction of elections outcome to the political space of any region in Nigeria depends on political party structures and voters’ decisions.